Children`S Tuberculosis of High Risk Groups in Samarkand Region of Uzbekistan (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In article the current situation reasons on tuberculosis among children are analyzed, new approach to identification of respiratory tuberculosis by a digital fluorography in the high risk groups is considered.